Algoritma Enkripsi Selektif Citra Digital dalam Ranah Frekuensi Berbasis Permutasi Chaos - Rinaldi Munir (Jurnal Rekayasa Elektrika, 2012)
This paper presents a selective image encryption in frequency domain. At first, the image is transformed into frequency domain with Discrete Cosine Transform (DCT), and then DCT coefficients are scanned in zigzag, and elements of the low-frequency sub-band are extracted. Encryption is performed only on selected elements by scrambling them using 2D chaos map, namely Arnold Cat Map. Next, IDCT is applied to obtain the encrypted image. The encryption algorithm is included in lossy encryption. Experiments on both grayscale images and color images show that the images can be encrypted succesfully. Histograms of the encrypted images differ significantly from histogram of the original images, and the pixels in the encrypted images are not longer correlated.